Fruit quality of ‘Eva’ e ‘Princesa’ apples grown under nitrogen fertigation in semiarid climate - João M. de S. Miranda; Ítalo H. L. Cavalcante; Inez V. de M. Oliveira; Paulo R. C. Lopes; Joston S. de Assis (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACTThe production of high quality fruits is a necessary factor for the adaptation and production of plant species with economic viability. Thus, an experiment was conducted from July 2012 to January 2013 to evaluate the fruit quality of the ‘Eva’ and ‘Princesa’ apple cultivars as a function of nitrogen fertilization in Petrolina, PE, Brazil. The experimental design consisted of randomized blocks, with treatments distributed in a factorial arrangement 2 x 4, corresponding to apple cultivars (Eva and Princesa) and nitrogen doses (40; 80; 120 and 160 kg of N ha-1), with four replications and three plants in each plot. The fruit characteristics, such as fruit mass, skin color (luminosity, chromaticity, and colour angle), size (width and length), pulp firmness, titratable acidity (TA), soluble solids (SS) and the SS/TA ratio, were recorded. Nitrogen doses do not affect fruit quality of studied apple cultivars. The fruit quality attributes are different between apple cultivars: fruit firmness, SS/TA ratio, fruit mass and fruit diameter are superior for Princesa cultivar, while the fruit length for Eva cultivar is superior.